Influence of the eggs of Ephestia kuehniella (Lepidoptera: Pyralidae) reared on different diets on the performance of the predatory bug Orius laevigatus (Hemiptera: Anthocoridae) - Serkan PEHLİVAN (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
The predatory bug, Orius laevigatus (Fieber, 1860) (Hemiptera: Anthocoridae), is an important biological control agent and widely used for augmentative biological control of the western flower thrips, Frankliniella occidentalis Pergande, 1895 (Thysanoptera: Thripidae) in greenhouse crops. This bug is generally reared using the Mediterranean flour moth, Ephestia kuehniella Zeller, 1879 (Lepidoptera: Pyralidae). The aim of this study was to determine the effects of E. kuehniella eggs produced by adult moths reared on different larval diets on the performance of O. laevigatus. The diets were 95% cornmeal + 5% yeast (CY diet), 53.3% cornmeal + 26.7% wheat bran + 15% Glycerine + 5% yeast (CBGY diet) and 53.3% wheat flour + 26.7% wheat bran + 15% Glycerine + 5% yeast (WBGY diet). Laboratory studies started with newly emerged nymphs of O. laevigatus kept in a climate chamber at 27°C, 60% relative humidity and a 14L :10D photoperiod. Eggs of E. kuheniella adults that were fed on one of the three different larval diets were provided to the nymphs as a source of food and bean pods of water. Following adult emergence, all individuals were sexed, and female and male pairs were put in plastic containers (30 cc) with eggs of E. kuehniella and bean pods. Nymphal development time, fecundity and longevity of O. laevigatus were not differently affected by feeding on the eggs of E. kuehniella reared on the three diets. In addition, the daily and total egg consumption of adults of O. laevigatus were similar. Because the CY diet eggs contain more nutrients, their consumption by nymphs was lower. This study indicates that the CY diet is an adequate diet for rearing E. kuehniella for producing eggs for rearing O. laevigatus.